Teaching strategies for cultivating preschoolers’ sharing behavior based on gender roles in Chinese culture - Yu Xiao; Maizura Yasin; Nor Aniza Ahmad; Norzihani Saharuddin (International Journal of Evaluation and Research in Education (IJERE), 2023)
Chinese boys and girls manifest distinct sharing behavior compared with children of other nationalities following different cross-national pathways. Undoubtedly, the Chinese traditional culture projects distinct expectations of female and male roles. Kindergarten teachers are responsible for delivering cultural norm knowledge to children and shaping their behaviors and beliefs. This study aims to provide an insight into how kindergarten teachers cultivate preschoolers’ sharing behavior considering the traditional gender-role culture in China. This study adopted the multiple case study approach and involved six participants working in a Chinese public provincial kindergarten in Hebei Province. The data collection techniques used comprise semi-structured interviews and document analysis. This study’s findings showed teachers develop both boys’ and girls’ sharing awareness through an other-oriented strategy. They also elicit sharing practices through benefits-oriented and habits-forming strategies. However, different treatments of boys and girls could be observed in some respects. These findings demonstrate that children’s sharing behaviors are shaped through the same strategy with a subtle gender bias. They further imply that the gender-role knowledge of Chinese kindergarten teachers impacts how they cultivate preschoolers’ sharing behavior.